The Manuscripts of Julius Eastman : Musical Notations, Time and Singularity - (:unkn) unknown (My University, 2021)
Julius EASTMAN (1940-1990) was an African-American composer who left a remarkable work, of which the current revival underestimates some fascinating aspects, including its very creative handwritten musical notation. This doctoral thesis is a study of sixteen musical manuscripts, on a total of about eighteen, left by Eastman. It is a first-hand study, carried out in part at University at Buffalo, where these musical archives are gathered. This study is mainly in three parts. At first, a methodological approach, aimed to build the adequate framework to consider the « object-manuscript ». The purpose here is to go beyond pragmatic readings (that of the « user-manual score »), to study the acts of writing as aesthetics acts to the fullest. Then, an original approach of each manuscripts scores, underlining the main evolutions, especially in the field of the notation of time and of the vocal parts, which seems to be two major issues. At last, a theoretical reflexion about what this study on Eastman brings to the uderstanding of what is, in general, the musical notation, faced with some important theories about writing of signs, images, spellings, etc. This study is sustained by a solid work about Eastman’s musical biography ; it contains a lot of comparisons between eastmanians ways of writing music and those of, among others in the Twentieth century, Schwitters, Ligeti, Berio, Berberian and Cage. Eastman’s radicality and singularity are described in its progressive construction. The Eastman’s original contribution in the notation and conception of time, which deeply concerns performers and actual composers, is described as a fundamental contribution in his legacy.
Keywords: African Research